Pengaruh media sosial : tiktok dalam tranformasi dakwah islam kontemporer: TIKTOK DALAM TRANFORMASI DAKWAH ISLAM KONTEMPORER - Ilmi, Arizha Mahirotul (Maliki Interdisciplinary Journal, 2024)
Social media has a huge impact on human life. This modern era is most often used by gen z one of them is tiktok. Currently there is a social phenomenon moral decline among the younger generation. This has led to various negative actions so that efforts need to be made to overcome this problem. the problem. These efforts can be realized through da’wah which is now carried out not only offline, but also online, namely through social media. not only offline, but also online, namely through social media. The focus of this research is to find out da’wah opportunities that can shape the positive character of teenagers in the digital era. shape the positive character of adolescents in the digital era. This research uses qualitative approach and descriptive type. In collecting data used literature research method (literature study). The results of this study indicate There are opportunities for da’wah in the digital era, especially through the TikTok application. The reason is, the majority of TikTok application users are teenagers and the platform also offers various features that help in making videos. platform also offers various features that help in making video sermons. sermon. Moreover, moral decadence among teenagers can be overcome through da’wah. da’wah. This shows that da’wah can form a positive personality in teenagers through the tiktok application.